Strategi Guru PAI Dalam Meningkatkan Minat Baca Al- Qur’an Pada Siswa Kelas VI Sekolah Dasar Negeri 18 Sange - Nurul Iman; Yayan Ridwan; Zuri Astari (Tarbiya Islamica, 2024)
This research aims to clearly describe: First, how PAI teachers plan strategies to increase interest in reading the Qur'an in class VI students. Second, what are the PAI teachers' strategies for increasing interest in reading the Qur'an in class VI students. Third, what factors influence PAI teachers in increasing interest in reading the Qur'an in class VI students at SD Negeri 18 Sange Duyung, Teluk Keramat District for the 2022/2023 academic year. This research uses qualitative methods with descriptive research type. Data collection techniques use interviews, observation and documentation, while data analysis techniques used are data collection, data reduction, data display and conclusions. The results of the research concluded that: PAI Teacher Strategy Planning in Increasing Interest in Reading the Qur'an in Class VI Students of SD Negeri 18 Sange Duyung is as follows: First, formulate learning objectives. Second, provide media and tools. Third, determine learning activities. Fourth, prepare a learning outcomes plan. PAI Teacher Strategy in Increasing Interest in Reading the Qur'an in Class VI Students, namely in the following way: Strategy used by PAI teachers in increasing interest in reading the Qur'an in students by getting into the habit of reading the Qur'an and memorizing it short suras of the Qur'an, this is done so that students become accustomed to reading the Qur'an, students become memorized by short surahs of the Qur'an and students can practice the contents of the Qur'an 'an as the holy book of Muslims. Factors that Influence PAI Teachers in Increasing Interest in Reading the Qur'an in Class VI Students Factors that influence PAI teachers in increasing interest in reading the Qur'an in students are internal factors and external factors, as for the internal factors: First, motivation. Both talents. Meanwhile, external factors: First, family. Two friends. Third family environment.